2016
DOI: 10.1167/iovs.15-18462
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Na+-K+-2ClCotransporter Activity in Rabbit Lacrimal Gland Duct Cells

Abstract: PurposeWe recently reported that isolated duct segments from rabbit lacrimal gland (LG) were able to secrete fluid in response to secretagogues, which were blocked completely by bumetanide. This suggests the functional involvement of Na+-K+-2Cl− cotransporter (NKCC1) in ductal fluid secretion. Therefore, the aim of this study was to investigate the activity profile of NKCC1 in isolated rabbit LG duct segments.MethodsInterlobular ducts were isolated from fresh rabbit LG tissue. Microfluorometry with the ammoniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The Ca 2+ -dependent K + channel identified in this study probably corresponds to the IKCa1 channel that we have identified on the apical membranes of rat lacrimal gland ducts. 7 The presence of this channel, along with the apical KCC1 transporter and CFTR, which have been identified immunohistochemically and functionally, 7,9,10,15,16 are consistent with evidence that the ducts secrete K + . The location of muscarinic receptors on the basal membrane of the duct cells, 7 and the demonstration by Katona et al 17 that isolated ducts secrete fluid in response to carbachol, support a mechanism in which cholinergic stimulation causes release of intracellular calcium 18 which activates IKCa1 channels, resulting in secretion of fluid rich in K + .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The Ca 2+ -dependent K + channel identified in this study probably corresponds to the IKCa1 channel that we have identified on the apical membranes of rat lacrimal gland ducts. 7 The presence of this channel, along with the apical KCC1 transporter and CFTR, which have been identified immunohistochemically and functionally, 7,9,10,15,16 are consistent with evidence that the ducts secrete K + . The location of muscarinic receptors on the basal membrane of the duct cells, 7 and the demonstration by Katona et al 17 that isolated ducts secrete fluid in response to carbachol, support a mechanism in which cholinergic stimulation causes release of intracellular calcium 18 which activates IKCa1 channels, resulting in secretion of fluid rich in K + .…”
Section: Discussionsupporting
confidence: 60%
“…7 The secretory properties of intact ducts have been described, and the data are consistent with the proposed model. [8][9][10] Electrophysiologic studies have characterized several K + and Cl-channels in lacrimal acinar cells, [11][12][13] however, due to their relative paucity and inaccessibility, the function of ion channels of duct cells has not been studied extensively. The goal of this project was to develop a method for isolation of viable, single duct cells and demonstrate their utility for patch-clamp recording by characterizing the properties of K + channels in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…The Delpire group reported similar results of both 86 Rb + and FluxOR methods [ 134 ]. Other techniques include the ammonium pulse technique which uses cardiac strips to measure the acidification rate [ 135 ]. A comparative analysis of measuring cation-chloride-cotransporter activity can be found in a review by Medina et al [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Delpire group reported similar results between 86 Rb + and FluxOR [115]. Other techniques include the ammonium pulse technique which uses cardiac strips to measure acidification rate [116]. A comparative analysis of measuring cation-chloridecotransporter activity can be found in a review by Medina et al [111].…”
Section: Box 1 Measuring Kcc3 and Nkcc1 Activity Ion-transport Activitymentioning
confidence: 94%